Incidence and risk factors for heart failure in the ELSA-Brasil cohort - Ana Paula de Oliveira Lédo; Sheila Maria Alvim Matos; Maria da Conceição Chagas de Almeida; Roque Aras (PLoS ONE, 2025)
Background Heart failure (HF) is a clinical condition with high morbidity and mortality and a growing impact on global public health. Longitudinal studies with large samples and extended follow-up are essential to understand its incidence and risk factors in diverse populations. Objective To estimate the incidence over time and identify factors associated with the development of HF among participants of the Longitudinal Study of Adult Health (ELSA-Brasil). Methods A cohort study with 14,854 ELSA-Brasil participants, followed for an average of 12.3 years. A total of 251 individuals with a previous diagnosis of HF at baseline (2008–2010) were excluded. Incident cases were identified in visits 2 (2012–2014) and 3 (2016–2018). Cumulative incidence and incidence rates were estimated. Bivariate comparisons were performed using the chi-square test, while multivariate analysis employed Cox regression to estimate crude and adjusted Hazard Ratios (HR) with 95% confidence intervals (95% CI). A statistical significance level of p < 0.05 was adopted. Results The incidence of HF was 1.35 per 1,000 person-years (1.39% cumulative) over visits 2 and 3, with 93 new cases in visit 2 (0.61 per 1,000 person-years; 0.63% cumulative) and 113 new cases in visit 3 (0.74 per 1,000 person-years; 0.76% cumulative). Incidence was higher among older adults (65–74 years), self-reported Black individuals, and those with excess weight. Advanced age and abdominal obesity were risk factors present in both visits, while Chagas disease, valvular heart disease, and smoking were specific predictors in visit 2, and hypertension, rheumatic fever, angina, and fatigue were predictors in visit 3. Conclusion The study highlights the progression of heart failure (HF) incidence and identifies important modifiable risk factors in the Brazilian population, reinforcing the need for preventive strategies and public policies focused on early detection and management of HF.